Coexisting protist-bacterial community accelerates protein transformation in microcosm experiments - Thao, Ngo V.; Obayashi, Yumiko; Yokokawa, Taichi; Suzuki, Satoru (Frontiers in Marine Science, 2014)
Proteins constitute the major portion of labile substances in the marine environment and are an important source of organic matter supporting marine ecosystems. However, previous studies have revealed that specific bacterial membrane proteins are refractory in the oceans. We here show by kinetic analyses of protease degradation activity using inactivated Pseudomonas aeruginosa (Pa) cells as a proteinaceous substrate that bacterial proteases are insufficient to completely hydrolyze proteins, which may partially cause the protein accumulation in seawater. Protease activity was monitored simultaneously in 8 microcosms subjected to differing conditions. Some Pa proteins were retained for 30 days in the presence of bacteria without protists, whereas the Pa proteins were completely disappeared in the presence of both, indicating that these proteins were substantially incorporated into protist biomass. Our result suggests that protists play an important role in the transformation of bacterial proteins in seawater. Our experiments also imply that the functional/taxonomic diversity should be taken into account when considering decomposition activity in marine environments.